1954
DOI: 10.1085/jgp.37.5.685
|View full text |Cite
|
Sign up to set email alerts
|

The Isolation of a Staphylococcal Phage Variant Susceptible to an Unusual Host Control

Abstract: A series of phage P1 variants was isolated from plaques developing on S. aureus WF 145. One in particular, phage 14, was studied in detail because its host range appeared to be dependent on the previous host of production; i.e., it was subject to a host control. When this phage was produced on host K1 its lysate assayed equally well on both 145 and K1 cells. When produced on host 145, however, it assayed manyfold higher on 145 than on host K1. All its particles adsorbed on K1 cells, but only a small percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
1

Year Published

1955
1955
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 5 publications
2
12
0
1
Order By: Relevance
“…The different patterns of reaction to the typing phages were often correlated with the presence in the culture of one, two or more different natural phages, in the same way as was shown in earlier work on Salmonella paratyphi-B (Nicolle, Hamon & Edlinger, 1951;Scholtens, 1950Scholtens, , 1952Felix & Callow, 1951). I n other instances differences in the content of the cultures of certain natural phages were observed, but these were not reflected by the pattern of reactions to the typing phages.…”
Section: I!psupporting
confidence: 72%
See 2 more Smart Citations
“…The different patterns of reaction to the typing phages were often correlated with the presence in the culture of one, two or more different natural phages, in the same way as was shown in earlier work on Salmonella paratyphi-B (Nicolle, Hamon & Edlinger, 1951;Scholtens, 1950Scholtens, , 1952Felix & Callow, 1951). I n other instances differences in the content of the cultures of certain natural phages were observed, but these were not reflected by the pattern of reactions to the typing phages.…”
Section: I!psupporting
confidence: 72%
“…paratyphi-B has provided other examples of the successful application as typing phages of preparations derived from natural phages which had not been subjected to any elaborate process of adaptation (Nicolle, Pavlatou & Diverneau, 1953, 1954Nicolle & Diverneau, 1955;Nicolle, Hamon & Edlinger, 1953;Scholtens, 1950Scholtens, , 1952Scholtens, , 1955a. These findings are in keeping with the view that the multiplicity of phage-systems applicable to any bacterial species is correlated with the multiplicity of enzyme-systems at work in that species (Felix, 1949(Felix, , 1953a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rippon (1952) described mutation of antigenic structure from group B to group F in the staphylococcal typing phage 42D. Ralston & Krueger (1954) produced evidence of phenotypic variation in host range of phage K (not a typing phage) dependent on the host used for its propagation.…”
mentioning
confidence: 99%
“…In previous work we have shown that two forms of the KI strain released the host-induced restriction of the polyvalent Ki4 phage (also designated Pia) which occurs during replication on staphylococci typing with group I1 phages (Ralston & Krueger, 1952,1954; Ralston & Baer, 1 9 6 4~) . Evidence is presented in this paper to indicate that propagation of the typing phages on these cultures of strain KI results in marked host-modified changes in phage host range so as to mask the original high efficiency of plating for their usual propagating host strain, thus altering the lytic group of the phages.…”
Section: Introductionmentioning
confidence: 99%